External knowledge modes and firm-level innovation performance: Empirical evidence from sub-Saharan Africa - Stephen Kehinde Medase; Shoaib Abdul Basit (Journal of Innovation & Knowledge (JIK), 2020)
This paper examines the significance of external knowledge sources as impacting factors on innovation by incorporating a variety of external sourcing strategies, the firm's internal competencies and the industry attributes, into a unique analytical framework in predicting the innovative capabilities of firms in developing countries. The World Bank Enterprise and Innovation follow-up dataset for manufacturing, service and retail firms in 11 countries in sub-Saharan Africa is utilised to assess the degree to which firms utilize external sources of information (customers, competitors, consultants, new employees and workshops) in the implementation of product, process, marketing and organizational innovation. Sectoral and country-specific estimations are performed with IV binary treatment and Tobit models, respectively. The findings demonstrate that, although internal sources are essential, external sources of information are also necessary to attain the desired level of innovativeness. These findings confirm the open innovation literature in that firms that open their innovation process and utilise distinct knowledge sources have a superior capability to introduce innovations. The paper provides significant contributions to the literature. The paper uncovers three sources of external knowledge linking indirect players in the market that are not common in the literature (consultant, new employees and workshop). The study shows that the baggage of knowledge inherent in these three sources is indeed essential to the innovative capabilities of the firms. Second, the results also reveal that the essentiality of external sources of knowledge differs conditional on the type of innovation considered (product, process, marketing or organisational), dependent variable operationalisation, sectoral, methodical configurations, and country specifics. Third, the study contributes to the understanding of how firms in emerging economies develop competencies for innovativeness through the interplay of knowledge from both direct and indirect market players. The findings offer essential insights on how management could invest in the distinct, useful and preferred external sources to best foster a compelling introduction of any innovation. The study further provides robust and novel evidence of the role of new consultants, employees and workshops on firms' propensity to innovate.
Keywords: 650; External knowledge modes; Innovation; Firm-Level; Developing countries; Competitors; Consultants; Customers; New employees; Workshops